Rituals and Worship of the Veddas: An Ethnographic Study Based on the Veddas Community of Batticaloa Vakarai region. - Srikanthan, S. (Eastern University, Sri Lanka, 2021)
Vagarai Veddas are recognized as archaic tribes whose identity is disappearing. Veddas have been living in Sri Lanka since prehistoric times. However, their cultural identities are undergoing rapid changes among the metamorphosing forces. However, rituals and related worship traditions occupy a prime position as a unique cultural symbol of Veddas social culture. In this case, this study aims to analyze the continuity and changes in rituals and religious worship traditions of Vakarai Pradesh Veddas. Rituals and worship are important cultural aspects of social life. Rituals and worship have become a form and culture that encompasses many elements of human society. Rituals and worship are seen as maintaining the heritage traditions and customs of the communities during the process of social change. Data for this study based on an ethnographic approach was collected through fieldwork in Vakarai area. All data collected were subjected to thematic analysis and discussed under appropriate subheadings. In this case, the primary issues such as the beliefs and worship of the Veddas community and their continuity and changes are discussed here in detail. It can be observed that ancestor worship and nature worship traditions continue in all aspects of the life of Veddas community of Vakarai region. However, changes in the worship traditions of the Veddas are taking place due to the government's settlements in the past, impacts due to the settlements, development projects, civil war, the resulting impacts, migrations of the Veddas, interactions with other communities, economic problems, change of period, etc. Through this research, it has been found that the traditions of worshiping gods based on Agama traditions are taking place, especially in combination with traditional worship traditions.
Keywords: Veddas; Primitive people; Rituals; Worship